Frontispiece: Applying Multivalent Biomolecular Interactions for Biosensors. Issue 72 (20th December 2018) - Choi, Hyeongjoo; Jung, Yongwon
Abstract : Multivalent biomolecular interactions are one of the universal principles in nature to achieve strong yet reversible (or dynamic) interactions between biological entities. Through a number of seriated and often weak bindings, gathered interaction pairs achieve highly enhanced binding affinities and also offer fundamentally different binding characteristics from corresponding monovalent pairs. In their Concept article onpage 19103 ff., H. Choi and Y. Jung discuss the current status of multivalent interaction studies and their progress in the biosensing area.